Strategic Corporate Communication dalam Proses Repositioning dan Rebranding - ., Prayudi; Juanita, Jana (Jurnal ILMU KOMUNIKASI, 2005)
Abstract: Global competition, price war, and fast growing of technology are among crucial factors that companies have to face as opportunities instead of constraints. Companies must adapt with changes based on vision and mission taht have been stated. Often, repositioning and rebranding has to be done in order to increase competitive advantage and strengthen compnany idnetity in the market place. Eventually, it is expected that companies’ stakeholders always aware and loyal towards product and company brands. This article examines the understanding of repositioning and rebranding within the context of strategic coprorate communication function.